Answer:
7
Step-by-step explanation:
Answer:
6x + 2(−2x + 1) = 22
Step-by-step explanation:
6x + 2(−2x + 1) = 22
This step can be used to solve by substitution method.
Answer:
(3,2)
Step-by-step explanation:
when reflecting across the x axis the y value becomes - while the x value stays the same
It rained on 15% of those days
Group together the like terms (plus 2x with 2x) (subtract 10 by 6)
4x+4=36
Move plus four to the other side as a negative
4x=32
Divide both sides by 4
32 divided by 4 is 8
Therefore, x is equal to 8